Ultrasonographic findings in normal temporomandibular joints Achados ultra-sonográficos em articulações temporomandibulares normais - Fernando Melhem Elias; Esther Goldenberg Birman; Cleide Kioco Matsuda; Ilka Regina de Souza Oliveira; Waldyr Antonio Jorge (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The purpose of this study was to determine some ultrasonographic standards of temporomandibular joints with normally positioned discs. Nineteen patients from 18 to 45 years old (average age: 27.4 years; 16 females and 3 males), with history of orofacial pain, but without clinical or radiological signs of disc displacement, underwent ultrasonography (US) and magnetic resonance imaging (MRI) for the examination of their joints. In 30 joints, the distance between the most lateral point of the articular capsule and the most lateral point of the mandibular condyle (lateral capsule-condyle distance) was measured, as well as the distance between the most anterior point of the articular capsule and the most anterior point of the mandibular condyle (anterior capsule-condyle distance). In the closed-mouth position, the average values found for the lateral capsule-condyle distance were 1.4 mm and 1.6 mm, respectively in the longitudinal (coronal) and transverse (axial) scans. In the open-mouth position, the average distance was 1.2 mm, in both longitudinal (coronal) and transverse (axial) scans. The average values found for the anterior capsule-condyle distance were 2.3 mm in the closed-mouth position and 1.1 mm in the open-mouth position, both in transverse (axial) scans. Intra-examiner agreement, measured in terms of the intraclass correlation coefficient, varied from 0.83 to 0.93. We believe that this study can contribute to the validation of US as a diagnostic method for temporomandibular joint disorders, provided that the obtained measurements be used in future studies as normal reference values. Este estudo teve o objetivo de determinar alguns padrões ultra-sonográficos de articulações temporomandibulares com discos normalmente posicionados. Dezenove pacientes com 18 a 45 anos de idade (média de 27,4 anos, sendo 16 do sexo feminino e 3 do masculino), com queixa de dor orofacial, mas sem sinais clínicos ou radiológicos de deslocamento do disco, foram submetidos à ultra-sonografia (US) e à ressonância magnética (RM) para avaliação de suas articulações temporomandibulares (ATMs). Em 30 ATMs, mediu-se a distância entre o ponto mais lateral da cápsula articular e o ponto mais lateral do côndilo mandibular (distância cápsula lateral-côndilo), bem como a distância entre o ponto mais anterior da cápsula articular e o ponto mais anterior do côndilo mandibular (distância cápsula anterior-côndilo). Na posição de boca fechada, as médias das medidas da distância cápsula lateral-côndilo foram 1,4 mm e 1,6 mm, respectivamente nos cortes longitudinal (coronal) e transversal (axial). Na posição de boca aberta, a média foi 1,2 mm, em ambos os cortes. As médias das medidas da distância cápsula anterior-côndilo foram 2,3 mm na posição de boca fechada e 1,1 mm na posição de boca aberta, ambas nos corte transversais (axiais). A concordância intra-examinador, medida pelo coeficiente de correlação intraclasse, variou entre 0,83 e 0,93. Nós acreditamos que este estudo pode contribuir para a validação da US como uma técnica diagnóstica das disfunções temporomandibulares, à medida que as medidas obtidas sejam utilizadas em estudos futuros como valores normais de referência.